Problems and Challenges related to Chiang Da Herbal Tea Community Enterprise, Doi Saket District, Chiang Mai Province, Thailand - Wungrath, Jukkrit; Khumai, Nuttida; Sutan, Piyawat; Khonchob, Phichayaket; Jongpuk, Manassanan (Nurture, 2022)
Purpose: The objective of this qualitative research is to report the problems and challenges related to Chiang Da herbal tea Community Enterprise (CE), Doi Saket District, Chiang Mai Province. Methodology: In-depth interviews (IDI) and Focus groups discussion (FGD) were conducted to obtain genuine comprehension from the CCE leader and members. The data were evaluated using content analysis. Finding: The finding was reported in 4 aspects of problems and challenges: 1) Human resources and membership, 2) marketing, 3) Budget, Finance, and Accounting and 4) Application of modern technology and information technology. The CCE member should develop knowledge and skills related to the issues mentioned above to be able to operate an enterprise group effectively. Practical implications: The government should play a role to promote and support the development of knowledge, skills, and capacity of the group by supporting policy, finance, equipment, and personnel providing advice. Furthermore, it is critical to use a successful community enterprise group as a model for learning and application. Contribution to literature: This study contributes to the existing literature as it is applied to other communities with similar characteristics and contexts, particularly community enterprises in rural areas that produce community products using local resources. The emphasis should be on developing the group members' potential.